Tumor progression locus 2 ablation suppressed hepatocellular carcinoma development by inhibiting hepatic inflammation and steatosis in mice. - Li, Xinli.; Liu, Chun.; Ip, Blanche C.; Hu, Kang-Quan.; Smith, Donald E.; Greenberg, Andrew S.; Wang, Xiang-Dong. (2016)
Background: Tumor progression locus 2 (TPL2), a serine-threonine kinase, functions as a critical regulator of inflammatory pathways and mediates oncogenic events. The potential role of Tpl2 in nonalcoholic fatty liver disease (NAFLD) associated hepatocellular carcinoma (HCC) development remains unknown.; Keywords: TPL2, HCC, Tumorigenesis, Inflammation, Steatosis.; Springer Open.